How efficiently does the EU support research and innovation in SMEs? - Carla Oliveira Henriques; Clara Viseu; Maria Neves; Ana Amaro; Maria Gouveia; António Trigo (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
The European Regional Development Fund devoted around 66 billion Euros to the financial support of innovation and productivity in European enterprises over the 2014-2020 programming period. In this framework, we assessed the implementation of the Operational Programmes dedicated to fostering research and innovation, particularly in small and medium-sized enterprises. With this aim, we used a network slack-based data envelopment analysis model paired with cluster analysis that encompasses a multitude of performance framework indicators to assess 53 Operational Programmes from 19 countries. Our findings suggest that compared to transition and less developed regions, more developed regions present a higher room for improvement. Also, less developed regions present a better performance when they employ their funding against more developed regions, suggesting that further funding should be channelled for leveraging research and innovation in the former regions. Finally, Operational Programme managers should focus on solving the problems both inherent to the poor outcomes in terms of enhancing the number of researchers working in improved research infrastructures and promoting the technology transfer between research institutions and enterprises.
Keywords: 650; cluster analysis; ERDF; EU regions; research and innovation; slack-based measure; SMEs